Polysulfide Speciation in the Bulk Electrolyte of a Lithium Sulfur Battery. Issue 5 (1st January 2018) - McBrayer, Josefine D.; Beechem, Thomas E.; Perdue, Brian R.; Apblett, Christopher A.; Garzon, Fernando H.
Abstract : In situ Raman microscopy was used to study polysulfide speciation in the bulk ether electrolyte during the discharge and charge of a Li-S electrochemical cell to assess the complex interplay between chemical and electrochemical reactions in solution. During discharge, long chain polysulfides and the S3 − radical appear in the electrolyte at 2.4 V indicating a rapid equilibrium of the dissociation reaction to form S3 − . When charging, however, an increase in the concentration of all polysulfide species was observed. This highlights the importance of the electrolyte to sulfur ratio and suggests a loss in the useful sulfur inventory from the cathode to the electrolyte.